2016
DOI: 10.1159/000453076
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Predictors of Allograft Dysfunction after Renal Transplantation in Children

Abstract: Background: The survival rates of renal transplant children are indeed on the rise, but it is still important to ensure that there is optimal renal function in these children in all their future growing years. The number of functioning nephrons and the graft ability to adapt to an increasing demand during body growth seem to be the most important factors for long-term allograft function. This study examined the long-term change in the glomerular filtration rate in a pediatric kidney transplant cohort and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…When we consider the burden of therapy required to maintain allograft function, the traditional approach of surgically treating only high‐grade transplant VUR with associated febrile UTI is supported by our finding that eGFR outcomes are similar in the hydronephrosis, febrile UTI, and abnormal renal biopsy groups. While the population in this study is small, the overall eGFR for the combined group is consistent with graft function based on historical controls . As shown by Weigel et al, there are multiple factors that affect graft function, and it is difficult to show that management of VUR alone will impact eGFR.…”
Section: Discussionmentioning
confidence: 47%
“…When we consider the burden of therapy required to maintain allograft function, the traditional approach of surgically treating only high‐grade transplant VUR with associated febrile UTI is supported by our finding that eGFR outcomes are similar in the hydronephrosis, febrile UTI, and abnormal renal biopsy groups. While the population in this study is small, the overall eGFR for the combined group is consistent with graft function based on historical controls . As shown by Weigel et al, there are multiple factors that affect graft function, and it is difficult to show that management of VUR alone will impact eGFR.…”
Section: Discussionmentioning
confidence: 47%
“…In another study on 67 pediatric kidney transplant recipients 10 an important risk factor for kidney failure in patients with CKD 24 and patients after kidney transplantation. 25 A multi-phasic eGFR trajectory with initial stability and subsequent decline can be expected in these events .…”
Section: Discussionmentioning
confidence: 99%
“…Episodes of rapid progression were more common in patients whose grafts subsequently failed, but nonlinearity was not associated with graft failure, probably due to the small number of patients in the cohort. In another study on 67 pediatric kidney transplant recipients 10 who underwent 278 inulin‐clearance measurements over a 10 year period, three trajectories of kidney allograft function, have been identified. The researchers have found that the “low and decreasing” trajectory pattern was more prevalent in recipients from deceased and older donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been an increased interest in examining renal function trajectories in CKD [13,14], there is little work in kidney transplantation [15]. Work from CKD groups and our own in renal transplant recipients [16] suggest that most patients do not experience linear renal function.…”
Section: Introductionmentioning
confidence: 99%